Beyond the weight: the role of parenting outcomes on childhood obesity over time - Mariana Filipa Guedes Costa (2022)
Over the last decade, the prevalence of childhood obesity (CO) has substantially increased, being estimated that 1/3 of Portuguese children are overweight (OW) or obese (O). From the several factors contributing to CO, parents/caregivers are highlighted as the main actors in shaping children's behaviors and lifestyles. The purposes of the current study were to: characterize the prevalence of childhood obesity in both assessment time points; explore the associations among parenting outcomes and family sociodemographic characteristics and obesity; test the moderation effect of the parenting variables on the relation between children's stantardized Body-Mass Index (BMI z-score) at both assessment time points. Participants were 128 parents of obese 5-to-12-years-old children, followed in an outpatient pediatric appointment in a Portuguese public hospital, where they receive intervention according to the European Society for Paediatric Gastroenteroloy Hepatoloy and Nutrition (ESPGHAN) guidelines. On the first assessment time point, parents completed self-reported measures on parenting behaviors and practices, psychological adjustment, and treatment self-regulation at baseline, and hetero-reported on the lifestyle-specific problems. Children's anthropometric measurements were evaluated at baseline and 3 to 6 months after. Results indicated na average decrease in the BMI z-score between evaluations. However, concerning the prevalence of OW/O, between both assessment time point, most of the children remained in the same category or changed to an inferior category. Results show an association between children's standardized Body Mass Index and parental outcomes, namely, poor monitoring, restriction, emotional correlates of being overweight, parental confidence, stress and external regulation, as well as some sociodemographic characteristics of the participants. Moreover, stress, parental confidence and external regulation were found to moderate the evolution of the BMI z-score over time.